PENGGUNAAN MEMBRAN ULTRAFILTRASI DALAM PEMBUATAN SARI BUAH RAMBUTAN - JOS, BAKTI; Susanto, Heru; Kuntolaksono, Satrio; Ariyanto, Yanuar (Universitas Diponegoro, 2010)
Abstract Â Hairy fruit (Nephelium sp) is fruit of horticultural belong in family Sapindacaeae. Membrane is a thin layer separates two phases which allow the displacement of specific components and hold other components that do not being needed. Ultrafiltration is a filtration process using membranes that filter out particles with a size of 20 to 1000 Angstrom. Results of ultrafiltration has high purity (0.4 to 0.6 NTU turbidity) than results from conventional manner (1.5-3 NTU turbidity). Yield gained was 5-8% higher than that gained from conventional. Dependent variable used is kind of hairy fruits (crops and cans). The independent variable is the pressure 2 kg/cm2, 3 kg/cm2, 0.4 kg/cm2, 0.5 kg/cm2, 0.6 kg/cm2 and the type of membrane (PES and hydrosart). The result of the study showed that greater operation pressure resulted in greater turbidity, and greater flux. The greater flux resulted smaller selectivity and pass the requirement of Environmental Protection Agency, USA. Â Key word : Hairy fruits, juice, membrane, ultrafiltration